(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
In this article, the author analyzes the factors determining the relevance of the electoral law and the process on the basis of historical data. Reveals the essence of the problem of suffrage, which for citizens should not be a profit. This is a civic duty and it is necessary to increase the spiritual value of this right. Some possible ways of reforming the electoral sphere are revealed, through training and ways of introducing a new look at the electoral right of a citizen. The conclusion of the article is the need to develop a curriculum for grades 10-11 to improve consciousness and literacy in electoral law and the process.